Analysis of the development of integration processes in the Eurasian Economic Union - Yessengeldin, B.S.; Tarshilova, L.S.; Sultanova, Z.Kh. (BUKETOV BUSINESS REVIEW, 2017)
The article addressed issues dealt with development of integrativeprocesses integration in Eurasian economic union. The purpose ofthe article was to study of degree of development of integration processes.The methodologies used are an analysis and synthesis, comparative and systematic approaches in research of current realities.Implemented analyze is given and questions of questions ofthe effectiveness of integration processes in the Eurasian Economic Union areconsidered in the article.Is indicated by authorsthat the emphasis ison regional integration processes,representing theworld trend asmost correct model of the strategic development.The dynamic developmentof trade in theEAEU countries was considered in detail.Sectoral orientation of thetrade is indicated. The main reasons ofreduction of mutual trade in dollar equivalent are shown. The analysis conducted above positive impact of economic integration on intra-industry trade. EAEUhas strengthened the economic relations betweencountries-participants. Econometric analysis of intra-industry trade‘s indexes shows that since the formation of Customs Unionquality of intra-industry trade is improving. Quantitative measures confirm totally EAEU‘s creation positive effect.